Circuit formation and sensory perception in the mouse olfactory system - Mori, Kensaku; Sakano, Hitoshi (Frontiers in Neural Circuits, 2024)
In the mouse olfactory system, odorants are detected with odorant receptors (ORs) expressed by olfactory sensory neurons (OSNs) in the olfactory epithelium (OE). Each individual OSN expresses only one functional OR gene, and OSN axons expressing the same OR species converge to a specific projection site forming a glomerular structure in the olfactory bulb (OB). Thus, odor signals are converted to a topographic map of activated glomeruli in the OB. Although the arrangement of glomeruli is genetically determined, the glomerular structure is plastic and can be modified by environmental odor stimuli in neonates. If the pups are exposed to a particular odorant, responding glomeruli become larger recruiting the dendrites of connecting projection neurons and interneurons. This imprinting not only increases the sensitivity to the exposed odor, but also imposes the positive quality on imprinted odor memory. External odor information represented as an odor map in the OB is then transmitted to the olfactory cortex (OC) for decision making to elicit behavioral outputs using two distinct neural pathways, innate and learned. Tufted cells (TCs) mediating learned decisions are activated earlier during inhalation, whereas mitral cells (MCs) for innate decisions are activated later in exhalation. Respiratory cycles are also correlated with processing of two types of olfactory signals, interoceptive and exteroceptive, using two pairs of mirror-symmetrical olfactory maps. In this paper, we will summarize the recent progress in the study of early olfactory inputs and neural circuit formation in mice.